2020
DOI: 10.1101/2020.09.28.317040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the origins of loss of protein function by analyzing the effects of thousands of variants on activity and abundance

Abstract: Understanding and predicting how amino acid substitutions affect proteins is key to practical uses of proteins, and to our basic understanding of protein function and evolution. Amino acid changes may affect protein function in a number of ways including direct perturbations of activity or indirect effects on protein folding and stability. We have analysed 6749 experimentally determined variant effects from multiplexed assays on abundance and activity in two proteins (NUDT15 and PTEN) to quantify these effects… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 93 publications
(167 reference statements)
16
41
0
Order By: Relevance
“…The data generated by MAVEs have been shown to help predict the status of pathogenic and benign variants, while also serving as useful benchmarks for computational variant classification methods ( Livesey and Marsh, 2020; Frazer et al, 2020 ). More generally, the data can also provide detailed insight into general aspects of protein structure and function ( Gray et al, 2017; Ahler et al, 2019b; Dunham and Beltrao, 2020; Chiasson et al, 2020; Starr et al, 2020; Cagiada et al, 2021; Amorosi et al, 2021 ). The extensive coverage of variants measured in the same assay provides a rich source of data that may be used for protein design, structure prediction and identification of crucial regions related to function and stability ( Stein et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data generated by MAVEs have been shown to help predict the status of pathogenic and benign variants, while also serving as useful benchmarks for computational variant classification methods ( Livesey and Marsh, 2020; Frazer et al, 2020 ). More generally, the data can also provide detailed insight into general aspects of protein structure and function ( Gray et al, 2017; Ahler et al, 2019b; Dunham and Beltrao, 2020; Chiasson et al, 2020; Starr et al, 2020; Cagiada et al, 2021; Amorosi et al, 2021 ). The extensive coverage of variants measured in the same assay provides a rich source of data that may be used for protein design, structure prediction and identification of crucial regions related to function and stability ( Stein et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the detailed relationship between protein stability and abundance is complicated and not fully understood ( Hingorani and Gierasch, 2014; Stein et al, 2019 ), we and others have shown that unstable proteins are often targeted for proteasomal degradation leading to lowered cellular abundance ( Nielsen et al, 2017; Chen et al, 2017; Nielsen et al, 2017; Scheller et al, 2019; Abildgaard et al, 2019; Nielsen et al, 2020 ). Thus, by combining the results from a VAMP-seq experiment with a MAVE probing protein activity it is possible to distinguish between variants that cause loss of function due to lowered abundance from those that change the intrinsic activity of a protein ( Jepsen et al, 2020; Chiasson et al, 2020; Cagiada et al, 2021; Amorosi et al, 2021 ). These experiments and analyses suggest that a relatively large fraction of variants that cause of loss-of-function are due to loss of stability and resulting degradation in the cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that Hsp110 should be further investigated as a potential therapeutic target to stabilize some ASPA variants and possibly other disease-linked missense protein variants. However, low abundance protein variants, including ASPA C152W, might also affect enzyme catalysis in addition to stability and/or folding [ 32 ], and therefore targeting molecular chaperones is not a universal therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it might be possible to uncouple loss of protein stability from loss of function [32], if components of the PQC system required for a protein's degradation can be identified and targeted. Since loss of protein stability is proposed to be a central cause of human diseases [33][34][35][36], this strategy holds wide-ranging therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%